Survey on Multi-Hop Communication To Enhance The Efficiency Of Sensor Node in WSN (International Journal of Engineering and Computer Science, 2018)
In WSN routing is the primary task for data communication between CHs to BS. The routing algorithm used should be energy efficient so that it can surmount related power constraints. As LEACH is energy efficient cluster based routing protocol used in Wireless sensor network, there are many version of LEACH one of them is MODLEACH. MODLEACH introducing efficient cluster head replacement scheme and dual transmitting power levels, However the efficiency of the MODLEACH can further be increased by introducing certain changes in the CH selection process and Multi-Hop communication between CH and BS. The cluster head selection is based on the probability and the threshold equation, but this may be problem for the next round. There is no concept that, it is based on nth power of energy conservation technique because cluster head selection not consider  any energy based parameter like residual energy of sensor node to be formed as CH